Remote monitoring of three-phase motor performance through Internet of Things integration with PZEM004T - Ulil Amri; muldi yuhendri (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Three-phase induction motors are critical components in various industrial applications, driving essential machinery and production processes. Ensuring optimal motor performance requires accurate monitoring of electrical parameters such as current and voltage. Conventional monitoring systems are often costly, inflexible, and lack real-time accessibility. This research proposes the design and implementation of a real-time current and voltage monitoring system for three-phase induction motors using the PZEM004T sensor integrated with the ESP8266 microcontroller and the Blynk IoT platform. The system employs three PZEM004T modules, each dedicated to one phase (R, S, T), to collect electrical data. These values are transmitted wirelessly via Wi-Fi and visualized on both a TFT LCD and the Blynk mobile application. Experimental results demonstrate that the system effectively captures and displays voltage and current values with high accuracy. The measurements for each phase showed consistent readings compared to standard instruments, with total power consumption measured at 1381.66 W and total current at 5.88 A. The system provides real-time data visualization and remote accessibility, enabling users to monitor motor status conveniently and take proactive measures against potential electrical faults. Furthermore, the integration of low-cost components and an open-source platform makes this system a practical solution for industrial environments seeking to enhance operational efficiency and reliability. This research highlights the potential of IoT-based monitoring systems in industrial motor applications and suggests that real-time visibility into motor performance can significantly improve energy management and preventive maintenance strategies.